2011
DOI: 10.1016/j.drugalcdep.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistent nicotine dependence among adults in the United States

Abstract: Background Evidence suggests that nicotine dependence is the key barrier to successful smoking cessation. No previous study has documented predictors of persistent nicotine dependence among adults in the community. The goal of this study is to prospectively identify predictors of continued nicotine dependence over a 3-year period among adults. Methods Data were drawn from Waves I and II of the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC), a nationally representative sample of 34,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 46 publications
9
52
2
2
Order By: Relevance
“…In addition, as shown previously, greater nicotine dependence was associated with anxiety (Goodwin et al 2011), and improvement in general health was associated with better mental health (Wise & Taylor, 1990;Sherbourne et al 1996;Patten, 2001;Ruo et al 2003;Evans et al 2005;Beard et al 2007;Janney et al 2008;Carek et al 2011).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, as shown previously, greater nicotine dependence was associated with anxiety (Goodwin et al 2011), and improvement in general health was associated with better mental health (Wise & Taylor, 1990;Sherbourne et al 1996;Patten, 2001;Ruo et al 2003;Evans et al 2005;Beard et al 2007;Janney et al 2008;Carek et al 2011).…”
Section: Discussionsupporting
confidence: 64%
“…Data from the majority of these studies lend consistent support for a strong relationship between nicotine dependence and depression (6,27,29,(34)(35)(36)48,(55)(56)(57). Overall, the findings suggest that adolescents and adults with past-year MDD, dysthymia, or depressive symptoms reported higher rates of current (6,27,(34)(35)(36)48,55,57) and lifetime (27) nicotine dependence than those without MDD, dysthymia, or depressive symptoms. In contrast, one study found no significant differences in the rate of lifetime nicotine dependence between those with and without an active diagnosis of dysthymia; however, significant associations between active MDD, preexisting MDD, and preexisting dysthymia and lifetime nicotine dependence emerged (29).…”
Section: Adolescentsmentioning
confidence: 65%
“…Mental illness is also predictive of persistent smoking (Goodwin, Pagura, Spiwak, Lemeshow, & Sareen, 2011), suggesting greater difficulty with RNC cigarettes in this population. Despite barriers to quitting, a significant number of smokers with comorbid disorders report wanting to quit (Weinberger, Desai, & McKee, 2010).…”
Section: Considerations Of Special Populationsmentioning
confidence: 90%